2015
DOI: 10.1002/pmic.201500131
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomics reveals differential regulation of protein expression in recipient myocardium after trilineage cardiovascular cell transplantation

Abstract: Intramyocardial transplantation of cardiomyocytes (CMs), endothelial cells (ECs), and smooth muscle cells (SMCs) derived from human induced pluripotent stem cells (hiPSCs) has beneficial effects on the post-infarction heart. However, the mechanisms underlying the functional improvements remain undefined. We employed large-scale label-free quantitative proteomics to identify proteins that were differentially regulated following cellular transplantation in a swine model of myocardial infarction (MI). We identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Recently, new molecular and cellular targets together with genomic, proteomic, and other biotechnological advances have led to the discovery of novel pharmaceutical agents for the treatment of MI [ 25 ]. Chang et al reported that the functional benefits of cell therapy were accompanied by differential regulation of protein expression in the recipient myocardium, which might contribute to the improved cardiac function [ 26 ]. The administration of growth factors, with the aim of promoting angiogenesis, chemotaxis, stem cell differentiation, cardiomyocyte survival and proliferation, reduction of apoptosis, and remodelling, holds great promise as a therapy for MI [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, new molecular and cellular targets together with genomic, proteomic, and other biotechnological advances have led to the discovery of novel pharmaceutical agents for the treatment of MI [ 25 ]. Chang et al reported that the functional benefits of cell therapy were accompanied by differential regulation of protein expression in the recipient myocardium, which might contribute to the improved cardiac function [ 26 ]. The administration of growth factors, with the aim of promoting angiogenesis, chemotaxis, stem cell differentiation, cardiomyocyte survival and proliferation, reduction of apoptosis, and remodelling, holds great promise as a therapy for MI [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, bottom-up proteomics typically does not distinguish protein isoforms with high sequence homology and may yield inconsistent results in the determination of protein expression especially in the label-free quantification using multiple peptides from the same protein (17). Therefore, antibody-based assays are often necessary for the validation of the protein expression changes obtained from the bottom-up proteomics data set (12,18,19).…”
Section: Simultaneous Quantification Of Protein Expression and Modifimentioning
confidence: 99%
“…It is important to point out that many truncated proteoforms of cTnI and cTnT have similar molecular weight as the intact proteoforms, therefore making the detection of such truncated proteoforms difficult and ambiguous via the gel electrophoresis approach. Moreover, although the conventional bottom- up approach is capable of identifying and quantifying thousands of proteins from a complex mixture [71, 72], due to limited sequence coverage as a result of proteolytic digestion, it remains challenging to distinguish highly homologous protein isoforms and proteolytic products with small truncation. On the contrary, top-down MS-based proteomics approach permits the analysis of intact proteins and unambiguously reveals the existing proteoforms including those with small truncation <1000 Da, as well as those with distinct sequence variations [73].…”
Section: Discussionmentioning
confidence: 99%